Novel chitosan-based flocculants for chromium and nickle removal in wastewater via integrated chelation and flocculation. (15th October 2019) - Sun, Yongjun; Chen, Aowen; Pan, Shu-Yuan; Sun, Wenquan; Zhu, Chengyu; Shah, Kinjal J.; Zheng, Huaili
Abstract: Carboxylated chitosan (CPCTS) is used as substrates in the design and synthesis of CPCTS-based flocculants through UV-initiated polymerization techniques. The synthesized flocculants are applied to remove Cr and Ni ions from chromic acid lotion and electroplating wastewater through two-stage flocculation. This study investigates the effect of flocculant dosage, pH, reaction time, and stirring speed on the removal efficiency of Cr and Ni ions. Results indicated that the total Cr removal ratios by CPCTS-graft-polyacrylamide-co-sodium xanthate (CAC) and CPCTS-graft-poly [acrylamide-2-Acrylamido-2-methylpropane sulfonic acid] (CPCTS-g-P(AM-AMPS)) are 94.7% and 94.6%, respectively. The total Ni removal efficiencies by CAC and CPCTS-g-P(AM-AMPS) are 99.3% and 99.4%, respectively. The two-stage flocculation with CPCTS-based flocculants could reduce the total concentrations of Cr and Ni to 1.0 mg/L and 0.5 mg/L, respectively. The relationship of removal capacity and structural properties between the flocculants with different functional groups is established through Fourier transform infrared spectroscopy, nuclear magnetic resonance, scanning electron microscopy, and X-ray diffraction. The micro-interfacial behavior between the colloidal particles and the solution during the integrated chelation–flocculation are elucidated. Thus, CPCTS-based flocculants could be a potential material for the removal of high amounts of Cr and Ni ions in industrial wastewater. Graphical abstract: Image 1 Highlights: Chitosan based flocculants with xanthate and sulfonic acid group were designed and synthesized. Flocculation process was used to treat industrial wastewater containing Cr and total Ni. Rapid Removal and Separation of Cr and total Ni was obtained by CAC. The micro-interfacial behavior during the integrated chelation–flocculation was elucidated. Chitosan based flocculants showed an excellent potential capacity for removing heavy metals.